PENGARUH PENDIDIKAN KEWIRAUSAHAAN TERHADAP INTENSI BERWIRAUSAHA MAHASISWA - Imron Burhan; Emmi Azis; Hasanuddin Hasanuddin; Kasmawati Kasmawati; Sandi Sandi (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
The purpose of this study is to determine the effect of entrepreneurship education on student entrepreneurial intentions. The approach used in this study is a quantitative approach. The measurement scale used in the questionnaire uses a Likert scale with 5 (five) answer choices. The population as well as the sample in this study were 35 students of the Bosowa polytechnic taxation study program. The data analysis method used in this study was simple linear regression analysis with the help of IBM SPSS Statistics 20 software. The results showed that the entrepreneurship education variable had a positive and significant effect on the entrepreneurial intention variable. The R Square value is 0.604 or 60.4% which indicates that the entrepreneurship education variable influences the entrepreneurial intention variable by 60.4%.